Antiviral activity of Ferula assa-feotida on HSV-1, 2 in vitro - Javad Charostad; Tahere Navidfar; Masoumeh Kiani; Paul Schinitzler; Akram Astani (Iranian Journal of Microbiology)
Background and Objectives: Medicinal plants are the primary treatment for many infectious and non-infectious diseases. In this study, we evaluated the antiviral activity of Ferula assa-feotida against herpes simplex viruses 1 and 2, and compared it with the antiviral drug acyclovir. Materials and Methods: In our experimental study, Ferula assa-feotida was dissolved in DMSO, then diluted in DMEM medium. Acyclovir was used at a concentration of 100 μM in all procedures. The antiherpetic activity and Antiviral activity of Ferula were evaluated in Vero cells (African green monkey kidney cells) by using the plaque reduction assay. Results: Inhibitory concentrations of 50% (IC50) of Ferula assa-feotida for HSV-1 and HSV-2 were determined at 0.00025% and 0.00015%, respectively. Ferula was introduced at various stages of viral infection and significantly inhibited HSV-1 and HSV-2 infectivity by > 95.5% and 89%, respectively, when virus was pre-treated before addition to the cells. No HSV-1 or HSV-2 activity was detected in cells treated prior to and following viral infection. Conclusion: These results indicate that Ferula assa-feotida demonstrates antiherpetic activity in the early phase of viral infection and could be used as potential antiviral agent.